Analysis Of Factors Affecting The Distribution Of People's Business Loans For The 2012-2020 Period - Thomas Firdaus Hutahaean; Carissa Komalasari; Inka Amelia Br Ambarita; Cynthia Tanika (Jurnal Mantik, 2022)
The country's economy is significantly assisted by banks because, as an institution, they facilitate the transfer of money in the form of deposits and loans to a large number of individuals. Most bank operations involve providing loans to local businesses and the general public. Inflation, interest rates, Gross Regional Domestic Product (GRDP), Non Performing Loans (NPL), and Capital Adequacy Ratio (CAR) are just a few examples of challenges faced by the business world in the lending process. This study is to assess the impact of factors such as inflation, interest rates, gross domestic product (GDP), non-performing loans (NPL), and credit availability on the distribution of People's Business Credit from 2012 to 2020. A quantitative approach has been taken for this study. This is known as the study of causal relationships between events. Indonesia Stock Exchange, there are 43 banking and financing companies listed between 2012 and 2020. In the period 2012-2020, the Indonesia Stock Exchange listed 23 banks. By using multiple linear regression test, the data were found. Based on the results of this data search, inflation has no effect on the company's lending for the 2012-2020 period. Interest rates have no influence on the distribution of KUR from 2012 to 2020. GRDP has an impact on the allocation of business loans during the period 2012-2020. For the period 2012-2020, non-performing loans did not have much influence on the distribution of People's Business Credit. CAR affects the company's credit distribution between 2012 and 2020. For the period 2012-2020 the distribution of People's Business Credit is influenced by inflation, interest rates, GRDP, NPL, and CAR.